2020
DOI: 10.3389/fendo.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fatty Acids on Bovine Oocyte Competence and Granulosa Cells

Abstract: Here we assessed the effects of dietary essential fatty acids on the developmental competence of oocytes in cows and on the functionality of follicular granulosa cells (GC). Lactating German Holstein cows were supplemented from week 9 ante partum (ap) until week 8 post-partum (pp) in four dietary groups designed as (i) control (CTRL: coconut oil), (ii) essential fatty acid (EFA: linseed and safflower oil), (iii) conjugated linoleic acid (CLA: Lutalin ®), and (iv) EFA+CLA (mixture of linseed oil, safflower oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Among other dietary FA, rumenic acid increases plasma concentration of insulin-like growth factor-1 (IGF-1) in cows and consequently promoting conception rates [379]. Recently, CLA was reported to affect follicular granulosa cells morphology and function, which may result in a compromised ovarian cyclicity and impaired fertility [380].…”
Section: Additional Effectsmentioning
confidence: 99%
“…Among other dietary FA, rumenic acid increases plasma concentration of insulin-like growth factor-1 (IGF-1) in cows and consequently promoting conception rates [379]. Recently, CLA was reported to affect follicular granulosa cells morphology and function, which may result in a compromised ovarian cyclicity and impaired fertility [380].…”
Section: Additional Effectsmentioning
confidence: 99%
“…However, in recent research, OA is reported to have adverse impacts on the steroidogenesis and morphology of bovine granulosa cells cultured in vitro [ 54 ]. Similarly, in vitro culture experiment involving bovine follicular granulosa cells revealed that α-linolenic acid (ALA) and LA inhibit the expression of genes associated with steroidogenesis in granulosa cells and lower the concentrations of secreted estradiol and progesterone [ 55 ]. But, the treatment of bovine granulosa cells with another functional fatty acid, DHA (docosahexaenoic acid), promoted granulosa cell proliferation as well as progesterone and estradiol secretion [ 56 ].…”
Section: Metabolism Of Functional Fatty Acids In Livestockmentioning
confidence: 99%
“…Dietary lipid supplementation is believed to enhance fertilizing potential in animals by increasing ovulatory follicle size, progesterone concentration in plasma and lifespan of corpus luteum (Sharma et al, 2020). Supplementing ruminants' diet with fats improves quality of the blastocysts obtained.…”
Section: Introductionmentioning
confidence: 99%